Characteristics and Outcomes of People With COPD Who Experience Exacerbations While on Inhaled Triple Therapy: Results of the SIRIUS I Cohort Study in the US (2015–2019) - Nordon C; Carstens D; Fagerås M; Müllerová H; Veeranki PS; Alves JA; Germack HD; Barnes TL; McCormack MC (International Journal of COPD, 2025)
Clementine Nordon,1 Donna Carstens,2 Malin Fagerås,3 Hana Müllerová,1 Phani S Veeranki,4 João André Alves,3 Hayley D Germack,2 Timothy L Barnes,4 Meredith C McCormack5 1Respiratory Evidence Strategy, BioPharmaceuticals Medical, AstraZeneca, Cambridge, UK; 2US Medical Evidence, Biopharmaceuticals, AstraZeneca, Wilmington, DE, USA; 3Global Medical, BioPharmaceuticals Medical, AstraZeneca, Gothenburg, Sweden; 4Value & Evidence Solutions, Optum Life Sciences, Eden Prairie, MN, USA; 5School of Medicine, Johns Hopkins Medicine, Baltimore, MA, USACorrespondence: Hana Müllerová, AstraZeneca UK, Academy House, 136 Hills Road, Cambridge, CB2 8PA, UK, Email hana.muellerova@astrazeneca.comPurpose: Many people with chronic obstructive pulmonary disease (COPD) continue to experience frequent moderate/severe exacerbations despite treatment with inhaled triple therapy (TT). We evaluated the baseline characteristics and outcomes (exacerbation rate, mortality, and healthcare resource utilization [HCRU]) of this COPD population, overall and by smoking status.Patients and methods: A retrospective real-world cohort study of US patients was conducted using Optum’s deidentified Market Clarity Data, an integrated claims and electronic health record database (study period: 2015– 2019). Patients eligible for inclusion were aged ≥ 40 years, with a COPD diagnosis, continuous 12-month (baseline) period of treatment with TT, and record of ≥ 2 moderate or ≥ 1 severe exacerbation during baseline. Follow-up was either variable (from end of baseline to death, loss to follow-up, or end of 2019) or fixed (12 months). Baseline characteristics and treatment patterns, crude incidence rates (IRs) for exacerbations and mortality (per 100 person-years [PYs]; variable follow-up), and HCRU and costs (12-month follow-up) were summarized descriptively.Results: Of 4,920 patients in the TT cohort, mean (SD) age was 62.3 (9.7) years, 60.9% were female, and 68.0% were white; 46.5% of TT cohort patients with a history of smoking were current smokers. Hypertension (92.7%), ischemic heart disease (52.1%), and heart failure (40.1%) were the most prevalent cardiovascular comorbidities. Most patients received oral corticosteroids (89.6%) or antibiotics (92.8%) for exacerbation management during baseline. Add-on therapies included phosphodiesterase-4 inhibitors (10.4%) and leukotriene receptor antagonists (26.4%). During follow-up, IRs (95% CI) were 108.2 (104.7– 111.8) per 100 PY for any moderate/severe exacerbation and 8.0 (7.4– 8.6) per 100 PY for mortality. Exacerbation risk was similar by smoking status. During the 12-month follow-up, mean (SD) all-cause and COPD costs were $63,178 ($77,061) and $26,153 ($47,085), respectively.Conclusion: There is high mortality and considerable HCRU and healthcare costs incurred by people with COPD experiencing frequent moderate/severe exacerbations while on TT. Optimization of COPD management and new therapies are needed to reduce disease burden in this population.Keywords: COPD, burden of illness, exacerbation, inhaled triple therapy, mortality, healthcare resource utilization